Community Service Language Learning: From Practice to Research - Ambrosio, Laura (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2025)
Based on an analysis of pedagogical practices, this article explains how community-based projects expand the learning space of university students enrolled in credit courses in French as a second language (FSL) or second language teaching (SLT). Community Service Learning (CSL), which is enriched by guided, progressive and regular critical reflection, enables students to take on the role of social actors who, using the target language, pursue the objectives of the course they take, while interacting authentically with the community of the target language.Positive psychology is the primary theoretical framework through which an exploratory qualitative analysis, based on a representative corpus of about 100 journals, has enabled us to identify seeds of autonomy, motivation, learning and self-confidence in language learning. We have also identified a correspondence between CSL and the development of transversal skills. Training future generations to engage in a greater sharing of experiences is a model of an experiential and action-oriented approach at the crossroads of research and practice.